Nurith Aviv 5 films, 1 livre = Śafah aḥat u-devarim aḥadim - Aviv, Nurith 1945- (Éd. Montparnasse, 2011)
Traduire: the last episode of a trilogy. It is a Babel-film, in which translators from different countries express themselves in their own languages, talk about their experience of passing on Hebraic literature written over the centuries: the Midrash, medieval Hebraic poetry, modern and contemporary literature. The translators speak with passion about the confrontation with a language, which sometimes leads them to transgress the rules of their own language"--http://en.unifrance.org/movie
Orig.: multilingual, subtitles: french, english, hebrew